Surgical treatment of complex aneurysms and thoracic aortic dissections with the Frozen Elephant Trunk technique - Dias,Ricardo Ribeiro (2015)
AbstractObjective:Report initial experience with the Frozen Elephant Trunk technique.Methods:From July 2009 to October 2013, Frozen Elephant Trunk technique was performed in 21 patients (66% male, mean age 56 ±11 years). They had type A aortic dissection (acute 9.6%, chronic 57.3%), type B (14.3%, all chronic) and complex aneurysms (19%). It was 9.5% of reoperations and 38% of associated procedures (25.3% miocardial revascularization, 25.3% replacement of aortic valve and 49.4% aortic valved graft). Aortic remodeling was evaluated comparing preoperative and most recent computed tomography scans. One hundred per cent of complete follow-up, mean time of 28 months.Results:In-hospital mortality of 14.2%, being 50% in acute type A aortic dissection, 8.3% in chronic type A aortic dissection, 33.3% in chronic type B aortic dissection and 0% in complex aneurysms. Mean times of cardiopulmonary bypass (152±24min), myocardial ischemia (115±31min) and selective cerebral perfusion (60±15min). Main complications were bleeding (14.2%), spinal cord injury (9.5%), stroke (4.7%), prolonged mechanical ventilation (4.7%) and acute renal failure (4.7%). The need for second-stage operation was 19%. False-lumen thrombosis was obtained in 80%.Conclusion:Frozen Elephant Trunk is a feasible technique and should be considered. The severity of the underlying disease justifies high mortality rates. The learning curve is a reality. This approach allows treatment of more than two segments at once. Nonetheless, if a second stage is made necessary, it is facilitated.